Sistema georreferenciado de indicadores de calidad de suelos para los Llanos Orientales de Colombia : Estudio de caso: Municipio de Puerto López, Meta - Rubiano Sanabria, Yolanda; Amézquita Collazos, Edgar; Beaulieu, Nathalie (2005)
The System Georeferenced of soil quality indicators for the savannas of Colombia. Geosoil allows to as much store, to consult and to process data of the soil as of his biophysics surroundings on different scales: parcel, property, community, municipality, department, region, and country. It operates from a relational database elaborated in ACCES 2000, composed by a series of structured main tables with information at different hierarchic levels that they allow the characterization of the properties of the soil. The morphologic and analytical elements of the ground are combined to conform indicators of quality by means of a qualification system that allows visualizing the degree and the number of limitations that could have a soil to be used in agriculture. In addition, it has modules in which the user can: (a) to add or to consult space characteristics and of attributes of the soil; (b) to visualize the interpretation of the quality indicators, grouped in limitation ranks; (c) to determine the general aptitude of the soil for a specific culture by means of the comparison between supply (soil) versus demands (requirements of the culture); (d) to calculate the fertilization necessities (e) to generate reports of the variability in depth of some characteristics, for one or more soil; (f) to map the results by means of a link with the MapMaker GIS (g) to visualize maps of space and/or temporary variability (isolines) of the variable used like indicator.